2013
DOI: 10.2147/opth.s50992
|View full text |Cite
|
Sign up to set email alerts
|

Changes in retinal nerve fiber layer and optic disc algorithms by optical coherence tomography in glaucomatous Arab subjects

Abstract: PurposeTo assess the difference in retinal nerve fiber layer (RNFL) and optic disc algorithms between glaucomatous and normal Arab subjects using optical coherence tomography (OCT).MethodsRNFL thickness and optic disc parameters were obtained in 65 patients aged 50.1 ± 7.7 years. Percentage differences in all parameters were calculated and analyzed between groups.ResultsThe mean RNFL thickness around the disc and at all quadrants was significantly thinner in glaucomatous eyes than in normal eyes (P < 0.01). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…In the studies by Repka and Quigly, Nilforoushan and Ahadi, and Pakravan et al, no significant correlations were observed between age and RNFL thickness. 20 – 23 In the current study, there was no significant difference in average RNFL thickness between male and female subjects, which is compatible with other reports. 5 , 13 , 14 , 20 , 24 Wong et al 25 reported significantly thicker RNFL values in men, and suggested that this finding was because of men’s higher body mass index.…”
Section: Discussionsupporting
confidence: 92%
“…In the studies by Repka and Quigly, Nilforoushan and Ahadi, and Pakravan et al, no significant correlations were observed between age and RNFL thickness. 20 – 23 In the current study, there was no significant difference in average RNFL thickness between male and female subjects, which is compatible with other reports. 5 , 13 , 14 , 20 , 24 Wong et al 25 reported significantly thicker RNFL values in men, and suggested that this finding was because of men’s higher body mass index.…”
Section: Discussionsupporting
confidence: 92%
“…Acquiring a scan of the entire optic nerve region is more difficult in children and automatic segmentation is not widely available. The advantage of volumetric imaging of the optic nerve region over single B-scan analysis, however, is that it captures arcuate retinal nerve fiber bundles in the superior and inferior quadrants, 12 , 13 often most susceptible to damage in optic nerve pathologies. It is not clear how feasible and reliable acquisition and analysis of the entire cpRNFL is in awake children.…”
Section: Introductionmentioning
confidence: 99%